Electrical bus performance modeling for urban environments - Perrotta, Deborah (2012)
Electric vehicles are seen as a key driver to address the issue of global warming, mainly through their zero tailpipeemissions operation and energy efficiency improvements. However, this does not solve the problem of urban chaos, relatedto traffic congestion and parking space cluttering, which contribute to increase human stress and overall economicproductivity decrease. To address all these issues, electric urban buses come as an obvious solution, and they also have theadvantages of being quieter than regular buses and of promoting a better travel experience to passengers.Nowadays there are already electric buses operating in some parts of the world and one of the main concerns is theirhigh weight, which is mainly due to the amount of batteries they carry in order to have an adequate range. Severalstrategies are possible and are being tested to provide buses with adequate operability in terms of range: battery swappingat central stations, battery charging at central stations on slow or fast charge rates and sizing the battery pack to the route ofthe electric bus using fast charge on bus stops.This paper intends to provide a mathematical model for the electric bus powertrain and its routes, based on a createddriving cycle that simulates an acceleration and deceleration period between two stops of a bus. The main objective is toverify how much of the energy recovered from regenerative braking can be absorbed by lithium-ion batteries and to verifywhether the supercapacitors can excel the batteries for this purpose. The intent is to reduce the amount of batteries carried,in the attempt to increase the bus efficiency by optimizing regenerative braking capabilities and possibly reduce overallsystem weight.